2020
DOI: 10.3389/fenvs.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Leaf Litter Quality During Its Decomposition in a Tropical Planted Mangrove Forest (Can Gio, Vietnam)

Abstract: Mangroves are highly productive ecosystems, being key components of trophic food chains along tropical coastlines. In Southern Vietnam, planted Rhizophora apiculata develops in the upper intertidal zone, while Avicennia alba naturally colonizes areas at lower elevation along tidal creeks. The main objective of this study was to quantify the seasonal variability of leaf litter decomposition rates considering that in previous studies we observed a strong influence of the monsoon on C and nutrients cycling within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…The sophisticated mechanisms in which K + is involved are pivotal for water- and nutrient-use efficiency, stress avoidance, and general plant homeostasis controls that imply several ecosystem-ecological consequences, such as species replacement or water- and nutrient-cycle variations in global change scenarios. As observed in several forests, such as temperate and tropical forests, K + is rapidly released during litter decomposition [ 204 , 205 , 206 ]. However, more than 70% of the initial K + content can be released during the first week of the decomposition process [ 207 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…The sophisticated mechanisms in which K + is involved are pivotal for water- and nutrient-use efficiency, stress avoidance, and general plant homeostasis controls that imply several ecosystem-ecological consequences, such as species replacement or water- and nutrient-cycle variations in global change scenarios. As observed in several forests, such as temperate and tropical forests, K + is rapidly released during litter decomposition [ 204 , 205 , 206 ]. However, more than 70% of the initial K + content can be released during the first week of the decomposition process [ 207 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…These results may suggest a greater contribution of mangrove porewaters to the tidal creek during the rainy season because of the larger volume of water exchanged between mangrove soils and mangrove creek, and because of a larger mangrove area immerged resulting from the higher water level. In addition, higher temperature during summer may also be involved, inducing enhanced processes of organic matter decomposition in mangrove soils as suggested in other studies (Taillardat et al, 2019;Vinh et al, 2020). Mangrove soils are most of the time anoxic (Kristensen et al, 2017), which is also the case for Can Gio (Thanh-Nho et al, 2019b;Vinh et al, 2019).…”
Section: Temporal Variability Of Mangrove Tidal Creek Characteristicsmentioning
confidence: 76%
“…We suggest that these higher concentrations were related to higher Mn D concentrations in porewaters ( Table 2). Vinh et al (2020) showed that during the rainy season, the elevated temperature and the high rainfall induced enhanced mineralization rates of leaf litter, which may have resulted in higher Mn D production in mangrove soils. In addition, during the rainy season, the water level of the river and thus of the tidal creek was higher.…”
Section: Manganese Dynamicmentioning
confidence: 99%
“…Previous literature has used mangrove plants and their sediments as reliable biological indicators to assess metal(loid) contamination and pollution (Defew et al 2005). Also, trace metal(loid)s are enriched during the decomposition of organic matter and can be absorbed in the water column at high tide and in surface sediments by organic molecules or decomposing litterfall (Vinh et al 2020).…”
Section: Introductionmentioning
confidence: 99%